Telemedicine and Digital Health in the Future of Midwifery Care - Astuti, Dhesi Ari; Langputeh, Prapaporn; Sulisworo, Dwi (Buletin Ilmu Kebidanan dan Keperawatan, 2023)
Telemedicine and digital health have emerged as transformative midwifery and maternal healthcare technologies. This study employs a comprehensive bibliometric analysis to explore the current research landscape at the intersection of telemedicine, digital health, and midwifery. The methodology involves an initial search in the Dimensions database using the keywords "Telemedicine AND Digital Health AND Midwifery", followed by data filtration based on publication year, article type, article category, and citation count. Further refinement is carried out using the Publish or Perish tool, which extends the search to capture additional relevant publications. Data obtained from Publish or Perish is then imported into VoSViewer for bibliometric analysis, enabling the identification of research gaps, trends, and clustering of topics within the selected literature. The study reveals a significant body of research on telemedicine and digital health in the context of midwifery, with a growing interest in the field. Health Sciences, Health Services and Systems, and Biomedical and Clinical Sciences emerge as the dominant research categories. Articles constitute the majority of publications, followed by chapters and edited books. The citation count indicates the influence and relevance of the identified literature. This study provides valuable insights into telemedicine, digital health, and midwifery research, highlighting areas of focus, research gaps, and emerging trends. The findings contribute to a better understanding of the evolving landscape in maternal healthcare, offering opportunities for further exploration and innovation in this critical domain.